STRATEGI PEMASARAN PRODUK KREDIT PERBANKAN (Kasus Bank Nagari Cabang Pekanbaru) - Yudhi Oktavianus; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Along with the development of banking institutions in the city of Pekanbaru with diverse product offerings as well as all the advantages given to make people have a lot of alternatives comparison to determine which banks will be selected . Competition in the provision of credit and the interest rate is also seen still small number of customers who receive credit in Bank Nagari Branch Pekanbaru . This is due to the lack of knowledge about the bank loan products villages . Based on field data collected from each respondent obtained the factors that influence the marketing strategies of Bank Nagari jackfruit branch road which in this study is divided into factors strengths and weaknesses . Factors that influence the strength in determining marketing strategies village bank credit can be seen as follows : a strategic location , being located at the center keramain and private and government offices and the interest rate offered is able to compete with other banks . Which is a factor that village bank weakness : The terms in the credit application that requires a lot of valid supporting evidence and the Administration also requires accurate data and also process credit search long enough .Excellent service from staff , because in serving customers with appropriate credit standards of customer service , marketing strategy Bank Nagari is located at coordinates ( 1.452 ; 3.215 ) . These results indicate the position of village bank marketing strategies are in quadrant I where the threat factor , so the marketing strategy shows a progressive strategy means the company is in good shape it is possible to continue to expand to increase growth and achieve maximum progress .Keywords ; Competition in interest rates , Strategy progressive , Bank Nagari